DETERMINATION OF VANADIUM IN BIOLOGICAL MATRICES BY FLAME ATOMIC-ABSORPTION SPECTROMETRY WITH ACTIVATED CARBON ENRICHMENT - YAMAN, M; GUCER, S (Springer Verlag, 1994)
For the determination of vanadium in biological materials by flame AAS an enrichment is described which comprises chelation with oxine and adsorption on activated carbon: The relative standard deviation for 10 mu g V/L was found to be 6% (n = 15).
Keywords: Raman Difference Spectroscopy; Frequency-Shifts; Spectra